EU Polar Cluster community meeting presentations from ASSW2023 - EU Polar Cluster members (Zenodo, 2023)
Presentations of the EU Polar Cluster members at the EU Polar Cluster community meeting on 18 February 2023, ASSW 2023, Vienna, Austria. Meeting title:European Coordination of Polar Research Abstract: The EU is a major contributor to Polar research that seeks to better understand the challenges the high North is facing in a rapidly changing environment. As part of this contribution, the EU established the EU Arctic Cluster, and was renamed the EU Polar Cluster with addition of Antarctic Projects in 2019. The Cluster is a growing network of EU-funded Polar research projects and organisations. Its work highlights excellent examples for improved cooperation and synergistic work of EU projects. The Cluster merges a broad spectrum of research and coordination activities and contributes with European-generated knowledge to both regional and global decision making. This event aims to provide an overview of the EU Polar Cluster and a panel discussion for the participating projects to share information. The presentations and the panel discussion will help the project find synergies, potentials for collaboration and also highlight research gaps that the EU should focus more on in the future. Thereby, this event aims to also provide strategic advice for new developments in Polar research funding.